Alliance formation: A Study of the Malaysian Automobile Supporting Industry - Ahmad Bashawir Abdul Ghani; Malcolm Tull (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2010)
Competition in global industries is shifting increasingly from inter-firm rivalry to rivalry between networks of firms. Strategies of individual firms are thus contingent on the degree of interdependence that exists between them and the parent firm in the network. The present study examines the effect of network affiliation on a member firm’s decision to enter a foreign market and international strategic alliance formation. Affiliate firms have two options available to them: (1) enter into a competitive strategic alliance with a competitor or (2) enter into a symbioticstrategic alliance with the parent firm of the network organiza-tion. We tested this assertion using data from archival sources on sixty-five Japanese automobile suppliers that had set up strategic alliances in Malaysia and that belonged to various inter-organizational networks. Results indicate that when affili-ate firms are dependent on the parent firm, they prefer to form symbiotic strategic alliances. Conversely, affiliate firms prefer competitive strategic alliances with competitors when they are not dependent on the parent firm. ALLIANCE FORMATIONA Study of the Malaysian Automobile Supporting IndustryKeywords: automobile industry; joint venture; mode of entry; networks; strategic alliances